Use of almond shell and almond hull as substrates for sweet pepper cultivation. Effects on fruit yield and mineral content - Valverde, M.; Madrid, R.; García, A. L.; Del Amor, F. M.; Rincón, L. F. (Spanish Journal of Agricultural Research, 2013)
The use of almond by products as substrate in greenhouses for growing vegetables has a great economic interest. The objective of this work was to assess the use of two almond by-products (almond shell-AS and almond hull-AH), which had been previously conditioned without composting, as substrates for pepper (cv. Caprino F1) production and to study their effects on the yield, fruit size, and fruit mineral content. Physical, physico-chemical, and chemical characteristics of the almond by-products were determined both initially and during the pepper growing season. Initially, all values of the parameters studied ― except sulfur and iron ― differed significantly between the two substrates. During cultivation, the 18 substrate parameters and variables tested - except bulk density - exhibited significant variations with time for AS; the same occurred for AH, exceptions being pH, total nitrogen Nt, N-NH4, bulk density, and manganese. The changes in both substrates for the K, N, and S concentrations were significant. The nutrient levels in AH were higher than for AS. The almond shell and almond hull substrates produced slight decreases in total fruit yield with respect to the control (0.79 and 3.22 for AS and AH, respectively), with a lesser decrease for AS, due to reductions in the number of fruits per plant rather than to reductions in individual fruit weight. The plants grown on the AS and AH substrates showed a decrease in total fruit yield, due to reductions in the number of fruits per plant rather than reductions in individual fruit weight.